ANALYSIS OF ZENITH WET DELAY (ZWD) CORRELATION WITH RIVER DISCHARGE IN NORTH BANDUNG AREA - Pramansyah, Arry
In a GPS survey study, the biases produced by the ionosphere and troposphere layers are known as ionospheric and troposphere biases. The method used in the determination of this troposphere bias is to use GPS inversion. This GPS inversion method is basically determining the magnitude of the distance deviation from the GPS satellites to the GPS receiver as a result of the delayed travel time during the signal passes through the troposphere layer. The distance deviation due to delayed travel time of GPS signals is commonly referred to as Zenith Tropospheric Delay (ZTD). ZTD is composed of two components, a dry component called Zenith Hydrostatic Delay (ZHD), and a wet component called Zenith Wet Delay (ZWD). The ZWD value has a positive correlation with water vapor and precipitation. Precipitation is related to the level of rainfall, and the level of rainfall can be seen from river discharge. The purpose of this study is to determine the magnitude of tropospheric wet delay using the (Global Positioning System) GPS and estimate the total variability of water vapor content in the troposphere. The methods used in the research include preliminary data processing and estimation of ZTD value using RTKLIB 2.4.2, determination of ZHD value by using Saatamoinen model, and extracting ZWD value from ZTD, by means of ZHD value using MATLAB software. Based on the previous researches it has been found that, the pattern of river flow over the Indonesian area follows the patterns of water vapor and rainfall which are influenced by the Australian and the Asian Monsoons, furthermore, the correlation between wet delay with the river discharge showing a very strong relationship. ZWD correlation with river discharge in North Bandung area showing a very strong results seen from the pearsonÃ‚Â’s correlation generated 88.84%, and t-students statistic test with 95% confidence level obtained that, there is a linear relationship between ZWD with river discharge in North Bandung area.